OPTIMIZATION OF INNOVATIVE BUSINESS PROCESSES IN THE VALUE CHAIN MANAGEMENT SYSTEM - RUDNICHENKO, Yevhenii; SKOROBOGATA, Larysa; MISHCHUK, Maxim (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines applied aspects of implementing the strategy of clustering the national economy based on the optimization of integrated value chains in the context of globalization challenges. The peculiarities of organizational-procedural and communicative-network support of business processes under the conditions of clustering of socio-economic systems are determined. The components of managing the processes of administration and implementation of the innovative potential of integrated production chains in the context of digital development and the format of optimization parameters were formed: intellectual capital; entrepreneurial potential; dominant technologies (level and possibilities of technology development in this area); industry localization (industry environment, market segments); information innovation infrastructure (environment of targeted integrated interaction).The evolution of the concept of integrated value chains in the context of their application in partnership activities of enterprises was considered, their mutual influence and combination, features and advantages were studied. The expediency of using the theory of digital business process management systems in business network structures and value chains is substantiated. The prospects for the use of integrated solutions are outlined, which allow creating a significant synergy of innovative network concepts, ensuring the overcoming of information asymmetry, and moving to an emergent level of business process management.Thus, the integrated value chain gradually expands from the production area to system processes in marketing, scientific and technical activities, financial support, sales process and service activities. A positive characteristic of this is the acquisition of invaluable experience in the systematic management of business processes and the implementation of innovative solutions to optimize the processes of increasing the value of enterprises in the strategic sector of the economy. Therefore, taking into account the current trends in the manifestation of innovative business processes in the digital administration system, one should possess the tools of the analog and digital management model when determining the profile of the business processes of filling the integrated value chain.
Keywords: business process; integration forms of production organization; value chain management; digital economy; integrated value chain